Marketing factors and consumer perception on purchase intention of organic products in Bintulu, Sarawak, Malaysia. - Ching, Janet Yeh Siew (2016)
Since few years ago, demand and interest towards organic products have increased significantly throughout the world due to the concern of human health, food safety and environmental friendly. The objective of this study is to investigate the relationship between marketing factors and perceptions of consumers on purchase intention for organic products. This research is conducted in Bintulu, Sarawak. Convenient sampling method is utilized in collecting the samples and multiple regression analysis is used to study the relationship between independent variables (marketing factors and consumers perception) and moderating factor (demographic factors) which was then hypothesized to the dependent variable (purchase intention). The finding showed that there is a significant relationship between marketing factors and consumers’ perceptions towards purchase intention. In terms of marketing factors, product availability, image and attribute show a significant relationship towards consumers’ purchase intention. However, price had no significant relationship towards purchase intention in this study which means that price is not really affecting the value that is perceived by the consumers. The price of the organic products might be used as an indicator of the product quality and as consumers’ investment for a healthy lifestyle. This study indicates that the consumers, who understand organic, concern about healthy lifestyle and perceive high value towards organic products, are more likely to develop intention towards organic products. Therefore, this finding gives insights into the practitioners, academician and policy makers to help them in different future perspective.